Diallyl disulfide (DADS) boosts TRAIL-Mediated apoptosis in colorectal cancer cells by inhibiting Bcl-2. (March 2019) - Kim, Hong Jun; Kang, Sanghee; Kim, Dae Yeoung; You, Sanguan; Park, Daeho; Oh, Sang Cheul; Lee, Dae-Hee
Abstract: Ever since several targeted agents were introduced a decade ago, progress in new therapeutic strategies for colorectal cancer (CRC) has been much slower than that for other cancers. Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is widely known to induce cellular apoptosis in numerous cancer cell types. However, many cancer cells are resistant to the effects of TRAIL, and thus, approaches are needed to overcome TRAIL resistance. We demonstrated that non-cytotoxic doses of diallyl disulfide (DADS) increased TRAIL-associated cell death in CRC cell lines. Additionally, synergistic effects between DADS and TRAIL were validated in vivo in nude mice. One process involved in these effects includes down-regulation of the anti-apoptotic protein Bcl-2, and the synergistic effect of DADS with TRAIL was attenuated in Bcl-2-over-expressing cells. Taken together, the results of this study give new insights into the role of DADS in TRAIL-related repression of CRC progression by inhibition of Bcl-2. Highlights: DADS at subtoxic doses effectively boosted TRAIL-related cell death in CRC cells. DADS caused CRC cell apoptosis by modulating TRAIL-induced caspase activation. Repression of Bcl-2 by DADS was demonstrated to be an essential step.